Evaluation of geriatric assessment in patients with chronic lymphocytic leukemia: Results of the CLL9 trial of the German CLL study group. Issue 4 (2nd April 2016) - Goede, Valentin; Bahlo, Jasmin; Chataline, Viktoria; Eichhorst, Barbara; Dürig, Jan; Stilgenbauer, Stephan; Kolb, Gerald; Honecker, Friedemann; Wedding, Ulrich; Hallek, Michael
Abstract: Multidimensional geriatric assessment (GA) has been demonstrated to predict outcomes in older patients with cancer. This study evaluated GA in a cohort of older patients with chronic lymphocytic leukemia (CLL). Seventy-five of 97 subjects with CLL who were enrolled in a clinical trial of the German CLL Study Group underwent GA prior to the start of study treatment (low-dose chemotherapy with fludarabine). GA included cumulative illness rating scale (CIRS), timed-up-and-go (TUG) test, dementia detection (DEMTECT) test and instrumental activities of daily living (IADL) index. There was little correlation between CIRS, TUG, DEMTECT or IADL results and treatment toxicity, feasibility or efficacy in this study. CIRS and IADL had no statistically significant impact on overall prognosis. However, under-performance in TUG or DEMTECT test was strongly associated with poor survival. The latter findings provide a rationale to further investigate geriatric assessment in CLL and in the context with other CLL treatments.